FISH HANDLING PROCESS LANDED AT ASEMDOYONG FISING PORT, PEMALANG REGENCY - Nabila Dinantiar Adelianoor; Fis Purwangka; Budhi Hascaryo Iskandar (Department of Fisheries Resources Utilization, Faculty of Fisheries and Marine Science, IPB University, Bogor, Indonesia, 2026)
Coastal Fisheries Port (PPP) Asemdoyong is the largest fishing ports in Pemalang Regency. This port provides various supporting facilities, including a Fish Auction Place (TPI). All fish handling activities, from loading and unloading on board to distribution carried out at this location. One of the important processes in determining the quality and price of fish are fish handling. This study aims to identify fish handling process carried out at PPP Asemdoyong,. This study was conducted in January 2026. The method used was using interview techniques and observation at PPP Asemdoyong. Data were analyzed using qualitative descriptive analysis. Based on the research results, the process of handling fishery products at PPP Asemdoyong, Pemalang Regency starts from preparation for loading and unloading, sorting fish on board and the fish auction place, the process of laying fish, purchasing and washing fish by local traders, purchasing fish by consumers, weighing fish to distributing fish to local markets and several regions in Indonesia. Some of the handling of fish catches at PPP Asemdoyong already based on SNI 2729 , especially for catch that will be distributed outside Pemalang Regency so the fish are maintained fresh. However, there are still some improvements are needed to maintain the quality of the fish. Key words: catch, fish handling, fish quality